Problematika Penerjemahan Bahasa Arab Ke Dalam Bahasa Indonesia Bagi Siswa Kelas V Di Madrasah Ibtidaiyah Darut Taqwa Sengonagung Purwosari Pasuruan - Fatkhur Rahman (Universitas Yudharta Pasuruan, 2017)
Arabic language learning, especially in translating many experiencing problems, then that becomes the problem formulation of this thesis is: What are the problems of translating Arabic into Indonesian language for students of classes V MI. Darut Taqwa Sengonagung? What efforts do students and teachers in addressing the problems of translating Arabic into Indonesian for students MI. Darut Taqwa Sengonagung? This type of research that I use in this paper is a field research (field research), which the authors plunge directly into the environment under study is Darut Taqwa Islamic Elementary School Sengonagung Purwosari Pasuruan. Efforts will be undertaken Arabic teacher in overcoming these difficulties, among others: a) Advise students to have Arabic dictionary. b) Advise to read books in Arabic and translating practice. c) Repeating lessons students are not yet understood or explained back and extending the exercise to translate. d) Provide better teaching complex sentences in position. While the efforts of the student in overcoming the problems of translation, namely: a) Attempt to have the Arabic-Indonesian dictionary also memorize Arabic vocabulary. b) Trying to master grammar theoretically and practically. c) Ask the teacher if experiencing difficulty in learning Arabic then attempted his own. d) Reading a book in Arabic is easy and translating practice.